BENTUK-BENTUK SINONIMI DAN ANTONIMI DALAM WACANA AUTOBIOGRAFI NARAPIDANA: KAJIAN ASPEK LEKSIKAL - Rani Setiawaty; Atiqa Sabardila; Markhamah Markhamah; Tri Santoso (STKIP PGRI SUMENEP, 2021)
This study aims to (1) identify synonymy and (2) antonym in prisoners' autobiographies. This research method uses descriptive qualitative. The data of this study are words, phrases, clauses and sentences that show synonymical and antonymy lexical cohesion tools. The data source was in the form of inmates' autobiographical texts in the Prison Class IA Surakarta. Data collection techniques with documentation, refer and note techniques. Data analysis techniques with the matching and agitating methods. The basic technique used in the padan method is the referential sorting technique. The basic technique used in the distribution method is the technique for direct elements (BUL) and advanced techniques in the form of dressing techniques. The results showed first, the use of synonyms in the form of words with more words than other types of synonyms. The use of word synonyms with words is 48%, followed by free morphemes with 16% bound morphemes, words with 12% phrases, words with 8% clauses, phrases with 8% phrases, and clauses with 8% clauses. Second, antonymy consists of absolute opposition 36%, polar opposition 33%, relationship 17%, hierarchy 7%, and compound 7%. Thus, absolute opposition is the most dominant type of antonym in prisoners' autobiographies.